Design Procedures for Series and Parallel Feedback Microwave DROs - Alaslami, Nauwaf (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2007.